Here to stay : uncovering South Asian American history - Rudra, Geetika (Rutgers University Press, 2022)
"There are 3.4 million South Asian-Americans in the U.S. They are creating an identity in a nation accustomed to binary racial choices, where the common understanding is that you are either black or white. The old model of immigration follows a progression from outsider to insider, or from being a person of color to either being perceived as white or being lumped in with white citizens. That transition has been documented with the help of two well known book titles: How the Irish Became White and How Jews Became White. Rudra argues that this typical pattern doesn't and can't apply to South Asian immigrants to the U.S. They are remarkably successful and well-educated residents, so they enjoy the privileges of whiteness without actually being white, while they continue to suffer discrimination (South Asian Muslims have a particularly difficult path toward acceptance). Author Geetika Rudra argues that it may no longer be necessary for minorities to be perceived white in order to succeed here on multiple levels. To explore South Asian identities, Rudra follows the influence of domestic immigration policies and international affairs for over a century. She starts her story in 1895, focusing on a particular immigrant who became the first South Asian-born naturalized U.S. citizen. For each of the five historical periods she covers, she has selected an exemplar--an actual historical figure -- whose story serves as an entryway to help explain evolving immigration policies and ethnic identity construction. Rudra explores how South Asian identity has veered toward and away from whiteness, allowing us to see the inherent artifice behind how American society has classified immigrant groups. She argues that the practice is more revealing about the construction of American identity than it is about American immigrant identity. Along the way, she also addresses the problem that there is not a single South Asian identity, since immigrants from the large geographical area that we call South Asia often have little in common"--